Pregnancy outcome in patients with intrahepatic cholestasis of pregnancy: an observational case control study - Maiti, G. D.; Pal, Arup Ratan; Jose, Tony; Saraswat, Monica (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Intrahepatic cholestasis of pregnancy (IHCP) is the most common cholestatic liver disease, which may impact the foeto-maternal health. The present study is conducted to determine various factors including maternal and neonatal outcome in IHCP comparing with the controls. Methods: In this prospective case control study, pregnancy with IHCP is compared with asymptomatic non-IHCP controls. Classical pruritus, icterus, elevated liver enzymes were considered in diagnostic criteria of IHCP. Dermatological lesion, acute or chronic liver disease, and other causes of pruritus were excluded from study. Results: Out of 100 patients, 50 cases and 50 controls were included in this study. Incidence of IHCP was seen 3.914% of which 66% were primi presented maximum at 31-33 weeks. 86% of IHCP responded to medication. Mean value of ALT, AST and ALP was found significantly raised (p value-<0.001) in IHCP patients. 66% in IHCP and 64% in non-IHCP group had normal delivery and remaining 34% and 36 % had caesarean delivery respectively. There was no significant increase in foetal distress or low Apgar (<7 at 5 min) at birth or adverse neonatal or maternal outcome in IHCP group. However, there was a statistically high meconium stained liquor (MSL), neonatal jaundice, IUGR and NICU admission were noted in the IHCP group in comparison to non-IHCP group. Conclusions: There is a significant incidence of IHCP in the obstetrical population. The biochemical changes, meconium stained liquor, neonatal jaundice, IUGR and NICU admission were significantly high in IHCP in pregnancy.